Effects of augmentation with \(Bacillus\) sp. DT1 on carbonfuran degradation and bacterial community in soil - Duc, Ha Danh; Tran Dat Huy,; Thi Thanh, Nguyen; Hong Vu, Ha Huynh; Thanh Hung, Nguyen; Ngoc Chau, Tran (Academia Journal of Biology, 2022)
Carbofuran is frequently applied to crop fields to combat insects globally causing serious environmental pollution. In this study, the enhanced degradation of carbofuran in soil by augmentation with Bacillus sp. DT1 was determined. The results showed that the augmentation with the bacterial strain increased the degradation by almost 30% compared to attenuation after 30 days at an initial concentration of 10 mg/kg dry soil. The half-life values of the insecticide were 41.6 and 17.9 days for attenuation and augmentation, respectively. Moreover, the augmentation with Bacillus sp. DT1 significantly increased sequence numbers of 16 S rRNA in soil compared to the initial stage. However, α-diversity indices, i.e., values of OTUs, ACE, Chao1 and Shannon showed no statistical differences in soil with and without the insecticide addition, with and without augmentation after 30 days. These results showed that carbofuran did not inhibit or stimulate the growth of soil bacteria at 10 mg/kg dry soil.